The Role of Notaries in the Implementation of Credit Agreements with Guarantee of Mortgage Rights - Susanto, Mellany Ayu; Adillah, Siti Ummu (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
The role of a Notary is needed to ensure that the implementation of the credit agreement runs smoothly. This study aims to analyze the role of a Notary in the implementation of a credit agreement with collateral rights at Bank BRI Unit Sendangmulyo and to identify the obstacles faced in the process. This study also seeks to find solutions to various obstacles that arise. The research approach method is sociological juridical. The research specification is descriptive analytical. The type of data uses primary and secondary data, the primary data collection method uses observation and interviews, and secondary data uses literature studies. The analysis method is qualitative descriptive analysis. The results of the study indicate that in running its business, Bank BRI Unit Sendangmulyo involves a Notary as a working partner. The Notary acts as a public official who is authorized to make authentic deeds for credit agreements, including deeds related to collateral rights. Meanwhile, obstacles from the Notary include obstacles from the Customer, obstacles from the Bank, and obstacles from the Notary. Obstacles originating from the Customer are the use of credit deviating from its original purpose. Efforts made in the form of policies in saving bad credit through rescheduling, reconditioning, restructuring. Obstacles from the Bank are negligence of bank officers, the Head of the credit section concerned is absent, and the distance between the Notary's office and the BRI Unit Sendangmulyo office is far. The effort is to urge Bank officers to be more focused. Obstacles from the Notary are the Notary's carelessness and the failure to change the name on the certificate used as the Mortgage Right and the accuracy of the promise by the debtor customer. The effort is to increase the Notary's caution and to check the documents before the credit agreement is signed to obtain certainty on behalf of the certificate and all parties must reach an agreement.